Pengaruh Desain Produk, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Sepatu Specs (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2019) - Scyndi Davitiyan Putra Ramadan; Nur Hidayati; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine and explain the effect of product design, price and brand image on purchasing decisions for shoes Specs case studies in students of the Faculty of Economics and Business, Islamic University of Malang class of 2019. The number of samples that were successfully collected was 100 respondents. While the analytical tool used is Multiple Linear Regression using SPSS. The results of this study are product design, price and brand image have a simultaneous effect on purchasing decisions and product design has a significant negative effect on purchasing decisions while price and brand image have a significant positive effect on purchasing decisions. Keywords: Product Design, Price, Brand Image, Purchasing Decision.